Students' Social Attitudes Towards Students with Disabilities and Social Guidance in Inclusive Elementary Schools - Yuwono, Joko; Wenas, Ren; Abdullah, Nazmin binti; Supratiwi, Mahardika; Anggarani, Fadjri Kirana; Tectona, Citra (Buletin Konseling Inovatif, 2025)
Teachers in elementary schools have a strategic role in providing social guidance to students to accept the presence of Students with Disability (SwD). The aims of this study were to determine the social attitudes of students, how teachers provide social guidance for non-disability students regarding the presence of disabled students in class/school and describe the challenges faced by teachers. This study uses a mixed method approach (Quantitative and Qualitative). This research method uses a data collection technique, namely a questionnaire distributed via Google Form to teachers in Indonesia. Through the questionnaire, quantitative data (percentage) and qualitative data were obtained regarding the challenges faced. The data were analyzed through descriptive statistics and qualitative analysis. Respondents in this study were elementary school teachers in inclusive elementary schools. A total of 173 elementary school teachers from 58 districts and cities. The results of the study showed that there were still many social attitudes of students towards the presence of SwD in inclusive elementary schools that were not good. Students are less able to accept the presence of SwD (51%). Most teachers have a way of guiding the form of advice to students (75%). Teachers have difficulty in providing social guidance to students with SwD. In providing social guidance, teachers face challenges of lack of information and teachers' ignorance about children with disabilities; teachers have difficulty in creating guidance models to help students who can’t yet accept SwD, increasing the independence of SwD, lack of training on guidance and counselling for SwD and dealing with parents.